Determinants of Transmission Risk During the Late Stage of the West African Ebola Epidemic. Issue 7 (3rd April 2019) - Robert, Alexis; Edmunds, W John; Watson, Conall H; Henao-Restrepo, Ana Maria; Gsell, Pierre-Stéphane; Williamson, Elizabeth; Longini, Ira M; Sakoba, Keïta; Kucharski, Adam J; Touré, Alhassane; Nadlaou, Sévérine Danmadji; Diallo, Boubacar; et al.
Abstract: Understanding risk factors for Ebola transmission is key for effective prediction and design of interventions. We used data on 860 cases in 129 chains of transmission from the latter half of the 2013–2016 Ebola epidemic in Guinea. Using negative binomial regression, we determined characteristics associated with the number of secondary cases resulting from each infected individual. We found that attending an Ebola treatment unit was associated with a 38% decrease in secondary cases (incidence rate ratio (IRR) = 0.62, 95% confidence interval (CI): 0.38, 0.99) among individuals that did not survive. Unsafe burial was associated with a higher number of secondary cases (IRR = 1.82, 95% CI: 1.10, 3.02). The average number of secondary cases was higher for the first generation of a transmission chain (mean = 1.77) compared with subsequent generations (mean = 0.70). Children were least likely to transmit (IRR = 0.35, 95% CI: 0.21, 0.57) compared with adults, whereas older adults were associated with higher numbers of secondary cases. Men were less likely to transmit than women (IRR = 0.71, 95% CI: 0.55, 0.93). This detailed surveillance data set provided an invaluable insight into transmission routes and risks. Our analysis highlights the key role that age, receiving treatment, and safe burial played in the spread of EVD.